Kissed By - Chasin, Alexandra (Book collections on Project MUSE., 2007)
"Set in New York, New England, Paris, and Morocco, this work is a collection of tales that are narrated by men and women, old and young, gay, straight, and bisexual; one narrator is not a person at all, but a work of art"--Provided by publisher